U-Pb ages of Gongga Shan granite, western Sichuan and its implication to the tectonic evolutions of eastern Tibet - Lee, Yuan-Hsi; Cook, Kristen L.; Tan, Xi-Bin; Chu, Mei-Fei; Chiu, Han-Yi; Li, Qui-Li; Shellnutt, J. Gregory; Xu, Xi-Wei (Frontiers in Earth Science, 2023)
The eastern margin of the Tibetan Plateau has given rise to much debate about mechanisms of plateau uplift and evolution and, in particular, the role of the lower crust in crustal thickening. Knowledge of the middle to lower crust conditions is critical for evaluating various models of crustal deformation, but data on crustal evolution through time are lacking. Here, we turn to the Gongga Shan granite, an intrusion along the Xianshuihe fault in easternmost Tibet that directly records local Cenozoic crustal conditions. We present 124 U-Pb samples from the Gongga Shan granite (GSG) that prove that the crust has been stepwise producing partial melt from 56 Ma to 4 Ma. According to the age distribution, the GSG can be separated into four major groups with ages of 4-10 Ma, 12-20 Ma, 25-40 Ma, and 43-56 Ma. Combining the timing information with geophysics and low-temperature thermochronology data, we suggest that events younger than 10 Ma may indicate the onset of recent crustal channel flow in the middle to lower crust. In contrast, the youngest 4 Ma ages indicate the ongoing partial melting of the middle crust. The 12-20 Ma events could be related to an earlier stage of crustal channel flow, consistent with the regional large-scale crustal channel flow in central Tibet.